Temperature and exposure time-dependent scintillation of Eu(III) polyoxometalate under X-ray excitation - Oliveira, Higor Henrique de Souza [UNESP]; Cebim, Marco Aurélio [UNESP]; Davolos, Marian Rosaly [UNESP] (Elsevier, 2018)
Sodium decatungstoeuropate, Na9[Eu(W5O18)2]·14H2O, is a promising material to convert X-ray into visible light. In this work, temperature and exposure time-dependent scintillation of the Na9[Eu(W5O18)2]·14H2O sample under X-ray excitation were evaluated. Light emission intensity decreases along with X-ray exposure time, probably due to electronic defects at (W5O18)6- groups, leading to a lower efficiency of the LMCT (O→W) process, which is determinant in the scintillation mechanism of this material. After X-ray exposition, there is a partial recovery of the initial emission intensity, indicating that defects created are reversible. With temperature increasing, changes in the emission spectra evidence the decreasing of the local symmetry around the Eu3+ ions, caused by reticular vibration and dehydration process. The luminescence intensity dependence with temperature suggests the possibility to use this material as molecular thermometer in two different temperatures ranges.
Keywords: Europium; Polyoxometalate; Scintillation; XEOL